The ins and outs of biosecurity: bird 'flu in East Anglia and the spatial representation of risk - Nerlich, Brigitte; Brown, Brian; Wright, Nick (Blackwell Publishing, 2009)
Avian influenza, or 'bird 'flu' arrived in Norfolk in April 2006 in the form of the low pathogenic strain H7N3. In February 2007 a highly pathogenic strain, H5N1, which can pose a risk to humans, was discovered in Suffolk. We examine how a local newspaper reported the outbreaks, focusing on the linguistic framing of biosecurity. Consistent with the growing concern with securitisation among policymakers, issues were discussed in terms of space (indoor–outdoor; local–global; national–international) and flows (movement, barriers and vectors) between spaces (farms, sheds and countries). The apportioning of blame along the lines of 'them and us'– Hungary and England – was tempered by the reporting on the Hungarian operations of the British poultry company. Explanations focused on indoor and outdoor farming and alleged breaches of biosecurity by the companies involved. As predicted by the idea of securitisation, risks were formulated as coming from outside the supposedly secure enclaves of poultry production.